Introduction to the Special Issue: “Advance in Recovery and Application of Bioactive Compounds from Seafood” - Charlotte Jacobsen; Susan L. Holdt (Foods, 2021)
Due to increased focus on a circular bioeconomy, full utilization of marine biomass, including side streams from the seafood processing industry as well as utilization of biomass that has not been used to a great extent in the Western world (e.g., seaweed), is receiving increased attention from both academia and industry. [...]